2017
DOI: 10.18632/oncotarget.19344
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review and clinical validation of circulating microRNAs as diagnostic biomarkers for colorectal cancer

Abstract: Because patients with colorectal cancer (CRC) are usually diagnosed at an advanced stage and current serum tumor markers have limited diagnostic efficacy, there is an urgent need to identify reliable diagnostic biomarkers. To better define the diagnostic potential of microRNAs (miRNAs) for CRC, we performed a comprehensive evaluation of reported circulating CRC miRNA markers. After a systematic literature review, we selected 30 candidate miRNAs and used quantitative real-time polymerase chain reaction to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…Previous studies have demonstrated that the expression level of miR-26b is reduced in the tissues of many cancers of liver, 40 breast, 41 and colon. 42 Functionally, miR-26b exerts a tumor-suppressive role in many types of cancer, and the miR-26b-mediated growth inhibition is achieved through suppression of target genes like OCT4, 43 SMAD1, CTGF, 44 and/or COX2. 45 In contrast, overexpression of miR-26a in a murine glioma model enhances de novo tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the expression level of miR-26b is reduced in the tissues of many cancers of liver, 40 breast, 41 and colon. 42 Functionally, miR-26b exerts a tumor-suppressive role in many types of cancer, and the miR-26b-mediated growth inhibition is achieved through suppression of target genes like OCT4, 43 SMAD1, CTGF, 44 and/or COX2. 45 In contrast, overexpression of miR-26a in a murine glioma model enhances de novo tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although it has been shown that the profile of circulating miRNAs has both diagnostic and prognostic potential, 17,18 recent works have confirmed inconsistency among multiple studies. 19,20 The authors suggest that this phenomenon could be explained by (1) utilization of different profiling methodologies, (2) small study groups, (3) greatly increased risk for type 1 error owing to the problem of multiple comparisons, and (4) confounding clinical effects affecting the responsiveness of miRNA expression to radiation-specific stimuli. Inconsistencies in circulating miRNAs in oncology studies can be also explained by methodological bias 21 and the overlapping effect of many physiological and pathophysiological processes, 22 but also by the different animal species used in the studies and highly heterogeneous study models (ie, different doses of radiation, irradiated sites, and assessed timepoints), and thus these inconsistencies require a systematic analysis of the results.…”
Section: Introductionmentioning
confidence: 99%
“…As the 3rd leading cause of tumor mortality, colorectal cancer is a well-known and well-studied type of cancer. The previous studies on colorectal cancer's biomarkers, surgery methods, metastatic mechanisms, target medicine-related researches, anesthesia methods, immune repertoires, all have revealed the fundamental data (Daher, Chouillard, & Panis, 2014;Deschoolmeester, Baay, Specenier, Lardon, & Vermorken, 2010;Pan et al, 2017;Tsai et al, 2010). Here, we recruited 19 CRC patients and five healthy controls to study the difference in immune repertoire status among colorectal cancer patient at preoperative, postoperative, and healthy controls.…”
Section: Comparison Of Trbv and Trbj Gene Repertoires Between Preopmentioning
confidence: 99%